Prawo rolne wobec współczesnych wyzwań - Budzinowski, Roman (Wydawnictwo Naukowe UAM, 2014)
The underlying assumption of the deliberations presented in this paper is that development of agricultural law is a result of the challenges and changing agricultural policies that agriculture has had to cope with over many past centuries. As a consequence, agricultural law has, on the one hand, been adopting to the changing environment, and on the other hand it was changing internally, passing through different stages of development. Today, the Resolution of the European Parliament and the Council of December 2013 setting out the legal framework of the common agricultural policy may be regarded as a response to the challenges which agriculture and food management are currently facing. The conclusion is, among others, that today agricultural law continues to demonstrate enormous adaptive potential. The best proof confirming this claim is that its scope has now gone beyond the strictly understood land matters and extended first, on the regulation of the organisation of an agricultural market, to subsequently include agro-industry, food and environmental issues, rural development and climate protection.

Alla base delle considerazioni svolte sta il presupposto secondo il quale lo sviluppo del diritto agrario è il risultato delle sfide poste davanti all’agricoltura nel corso dei secoli e – su questo sfondo – soprattutto davanti alla politica la quale decideva del modo in cui andavano affrontate. Il diritto agrario ha risposto alle mutevoli sfide della modernità così come veniva intesa in un dato momento o luogo, ma al contempo ha subito modifiche, attraversando varie fasi di sviluppo. I regolamenti del Parlamento europeo e del Consiglio (UE) del dicembre 2013, i quali determinano il quadro normativo della Politica Agricola Comune per gli anni 2014-2020, possono essere trattati in qualità di risposta alle sfide poste davanti all’agricoltura ed all’economia agroalimentare. In conclusione l’autore afferma tra l’altro che il diritto agrario ha dimostrato e continua a dimostrare una notevole capacità di adattamento, la quale si manifesta nel cambiamento dei confini di questo diritto, nell’andare al di là della problematica della terra, nell’includere l’organizzazione del mercato agricolo nella regolazione giuridica, e successivamente anche la problematica agroalimentare e agroambientale, in riferimento allo sviluppo delle zone rurali e alla tutela del clima.
Challenges facing agricultural law today
Diritto agrario di fronte alle sfide contemporanee